Assessing Forest Governance : A Practical Guide to Data Collection, Analysis and Use - Cowling, Phil (World Bank, Washington, DC and FAO, Rome, 2014)
In the last twenty years, practitioners have come to appreciate that governance is often the weak link in addressing unsustainable use of forests and trees. Technical knowledge alone is insufficient, and no natural forest management, protected area, plantation, or agro-forestry project will succeed if the resources are poorly governed. The concept of "forest governance" is often difficult to grasp because many laws, rules, policies, actions, and interactions shape forests. This also makes it difficult to be clear about what the major governance impediments are and what to do about them. The guide is the outcome of a collaboration of experts from organizations with different views and roles on governance issues who united to direct the compilation of a common set of good assessment practices. This guide presents a step-by-step approach to planning forest governance assessment or monitoring, collecting data, analyzing it, and making the results available to decision makers and other stakeholders. It also presents five case studies to illustrate how assessment or monitoring initiatives have applied the steps in practice, and it includes references and links to dozens of sources of further information.